Modular Enzymatic Cascade Synthesis of Nucleotides Using a (d)ATP Regeneration System - Fehlau, Maryke; Kaspar, Felix; Hellendahl, Katja F.; Schollmeyer, Julia; Neubauer, Peter; Wagner, Anke (Frontiers in Bioengineering and Biotechnology, 2020)
Nucleoside-5’-triphosphates (NTPs) and their analogues are building blocks of DNA and are important compounds in both pharmaceutical and molecular biology applications. Currently, commercially available base or sugar modified NTPs are mainly synthesized chemically. Since the chemical production of NTPs is time-consuming and generally inefficient, alternative approaches are under development. Here we present a simple, efficient and generalizable enzymatic synthesis method for the conversion of nucleosides to NTPs. Our one-pot method is modular, applicable to a wide range of natural and modified nucleotide products and accesses NTPs directly from cheap nucleoside precursors. Nucleoside kinases, nucleoside monophosphate (NMP) kinases and a nucleoside diphosphate (NDP) kinase were applied as biocatalysts. Enzymes with different substrate specificities were combined to produce derivatives of adenosine and cytidine triphosphate with conversions of 4 to 26%. The implementation of a (deoxy)ATP recycling system resulted in a significant increase in the conversion to all NTP products, furnishing 4 different NTPs in quantitative conversion. Natural (deoxy)NTPs were synthesized with 60 to > 99% conversion and sugar- and base-modified NTPs were produced with 69 to > 99% and 27 to 75% conversion, respectively. The presented method is suitable for the efficient synthesis of a wide range of natural and modified NTPs in a sustainable one-pot process.